Sustainable Accounting through Ind AS 116 – An Investigation - Farzana J , Fathima; Vignesh B (International Journal of Psychosocial Rehabilitation, 2020)
Economic Reforms 1991 had a great impact on Indian economy, leading to more footage of foreign companies and foreign investors in India. According to FDI (Foreign direct investment) policy 2005 India permits 100 percent FDI in its ventures. India earns major inflow of foreign currency through its IT sector and is one among the top exporter of IT in the world. With these accolades India attracts more FDI. As the investors are from varied Nations, demand for uniform reporting of financial statements emerged, in order to facilitate understandability and reliability of the published reports of the companies. Hence, to establish harmonisation in financial reporting, India Adopted IFRS (International Financial Reporting Standards) with convergence of Indian Accounting Standards, named as Ind AS. Due to ICAI’s (Institute of Chartered Accountant of India) membership in IASB (International Accounting Standard Board), until now 42 Accounting Standards were adopted in India. Among them Ind AS 116 ‘Leases’ was the latest adopted standard through MCA (Ministry Of Corporate Affairs) with effect from 1st April 2019. The application of these accounting standards enhanced the reliability of financial statements and ensured sustainability in accounting. Hence, this present paper focus on the implication of Ind AS 116 on selected Indian IT companies namely, Infosys technologies, Wipro Technologies and Siffy Technologies. Lease accounting has a major impact on the financial statements of the companies as majority of companies do not prefer to block huge investments by purchasing own property. Further the paper also discusses the requisite to adopt this standard in India successfully. A detail note on the impact of this standard considering measurement metrics were reviewed and added to it the effect of lease (only) was shown in a projected consolidated financial statement and projected standalone financial statement of the stated companies, to get a clear representation.